Evaluating the effects of antidepressant medication on post-operative outcomes in lower body contouring surgery after massive weight loss: A retrospective study - Pajula, Susanna; Veräjänkorva, Esko; Koljonen, Virve; Karukivi, Max (Elsevier, 2026)
Background
Postoperative complications are common following lower body contouring surgery (LBCS) after massive weight loss (MWL). This study aimed to determine whether antidepressant use is associated with the occurrence of complications after LBCS.
Materials and Methods
This retrospective study included consecutive patients who underwent LBCS after MWL at Turku University Hospital in Finland between 2016 and 2021. Weight loss was achieved either through bariatric surgery (BS) or lifestyle modifications.
Results
A total of 150 patients were included, with a mean age of 45.8 ± 11.1 years. The majority were women, 128 (85.3 %), and 22 (14.7 %) were men. Most patients (71.3 %) underwent BS. Antidepressant use was reported in 33 patients (22 %). Compared to non-users, antidepressant users were older (49.1 vs. 44.8 years, p = 0.05) and had a significantly higher body mass index (BMI) at the time of LBCS (29.5 ± 5.5 vs. 27.8 ± 3.0 kg/m², p = 0.02). The overall complication rate was 51.3 %. Patients on antidepressants had a 4.4-fold increased risk of developing deep tissue infection after surgery (aOR 4.36, 95 % CI: [1.08–17.71], p = 0.04) and were over five times more likely to be rehospitalized for intravenous antibiotic treatment (aOR 5.07, 95 % CI: [1.28–20.02], p = 0.02) than those who did not use antidepressants.
Conclusion
Antidepressant use was associated with a higher risk of deep tissue infection. Whether these findings are due to the antidepressant or the underlying psychiatric condition remains unclear. Future studies should investigate the relative contributions of these factors to optimize the care of patients with a history of MWL who undergo LBCS.